Final answer:
The zeros of the function y=-2(x-2)(x-10) are x=2 and x=10, as setting y to zero and solving the factored expression for x gives these solutions.
Step-by-step explanation:
To find the zeros of the given function y=-2(x-2)(x-10), we need to set the function equal to zero and solve for x. This means we look for values of x that make the expression on the right-hand side of the equation equal to zero.
Setting y to zero gives the equation:
0 = -2(x-2)(x-10).
Since the expression is already factored, we can directly set each factor equal to zero:
(x-2) = 0 or (x-10) = 0.
Solving these two simple equations gives us the zeros of the function: